Study of sociodemographic factors of women undergoing caesarean section in tertiary care centre of rural area of central India - Jain, Shuchi M.; Thool, Ketki; Shivkumar, Poonam V.; Jain, Manish A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Many studies have attempted to examine and evaluate the changes in population characteristics that may have contributed to the observed increase in CS rate. The aim of this study was to determine the caesarean section rate and demographic characteristics of women undergoing caesarean section in our rural tertiary health centre of central India. Methods: This prospective study was conducted in department of obstetrics and gynecology. The study instrument comprised a pre-structured data collection proforma which had various sections; social demographic characteristics, obstetric history and gestation details. Results: The overall caesarean section rate (CSR) was 36.88%. Maximum women (39.62%) who underwent Caesarean section were of age group 25-29 years. 58.05% from rural while 41.95% from urban area. CS was more in women of lower middle (22.80%) and upper lower (20.80%) class. Majority of women who had caesarean section were educated till higher school (31.87%) or were graduate (22.61%), 5.85% were illiterate. Majority of women (56.40%) were housewives. CSR was 70.83% in referred and 28.31% in booked. 52.86% women were nulliparous. Caesarean section was maximum (83%) in term, 16.92% preterm women and 0.08% post term women. 38.69% were referred from other health facilities. Maximum referrals 43.21% were from the district hospital. Conclusions: It was noted that the preference for caesarean section is more in women of 25-29 years, lower middle and upper middle class, rural women, educated upto high school and housewives at our centre. This hospital also serves as referral centre from surrounding health facilities increasing the caesarean section rate of the institute.